Comparison of periodontal open flap debridement versus closed debridement with Er, Cr:YSGG laser. (27th February 2013) - Gupta, M; Lamba, AK; Verma, M; Faraz, F; Tandon, S; Chawla, K; Koli, DK
Abstract Background Traditional periodontal open flap debridement (OFD) results in reduced pocket depth (PD), clinical attachment loss (CAL), gingival recession (GR) and postoperative pain and discomfort. The quest to overcome these shortcomings has led to research into Er, Cr:YSGG laser assisted pocket therapy (ELAPT). This study was designed to compare the clinical outcomes of ELAPT versus OFD. Methods Fifteen patients with a PD of ≥5 mm and ≤8 mm at two sites were selected. Test sites (Group 1) were treated by ELAPT and the control (Group 2) by OFD. Clinical parameters were recorded at baseline, 3 and 6 months and included Plaque Index (PI), Gingival Index (GI), modified Sulcular Bleeding Index (mSBI), PD, CAL and GR. Results Both treatments produced a reduction in PI, GI, mSBI and PD, an increase in GR, and a gain in CAL at 3 and 6 months. The mean gain of CAL in Group 1 at 3 and 6 months (1.60 ± 0.78 and 1.80 ± 0.63) was similar (p > 0.05) to the value of Group 2 (1.93 ± 0.88 and 2.00 ± 0.54). GR increased significantly (p < 0.05) only in Group 2 at 3 and 6 months (1.80 ± 0.56 and 1.87 ± 0.64) compared to Group 1 (0.50 ± 0.68 and 0.60 ± 0.74). Conclusions ELAPT compared with OFD results in similar CAL gains with less GR and significant reductions in PD, GI and mSBI, and may be considered as an alternative to surgical therapy.